Multiplex PCR for detection of Chlamydia trachomatis and Neisseria gonorrhoeae in Genitourinary specimens. - Mahony, J B (1995)
We developed a multiplex PCR (M-PCR) assay for the simultaneous detection of Chlamydia trachomatis and Neisseria gonorrhoeae. M-PCR employed C. trachomatis-specific primers KL1-KL2 and N. gonorrhoeae-specific primers HO1-HO3 and produced products of 241 and 390 bp, respectively. PCR products were easily detected by agarose gel electrophoresis and confirmed by Southern hybridization using labelled oligonucleotide probes. M-PCR had a sensitivity of 10 fg of C. trachomatis and N. gonorrhoeae DNA (equivalent to 1 to 2 genome copies). M-PCR detected the presence of C. trachomatis and N. gonorrhoeae DNA in 15 male urethral and 12 female endocervical specimens, 3 of which were positive for C. trachomatis, 18 of which were positive for N. gonorrhoeae and 6 of which were positive for both organisms. M-PCR was evaluated further by testing 200 male first void urine (FVU) specimens, of which 18 were positive by C. trachomatis PCR and Chlamydiazyme and 4 were positive by C. trachomatis PCR but negative by Chlamydiazyme. All 22 FVU specimens were positive by a confirmatory PCR using a second plasmid target and were positive by M-PCR. Ten of 11 men with cultures that were positive for N. gonorrhoeae had FVU specimens that were positive by both N. gonorrhoeae PCR and M-PCR. Two other men with negative N. gonorrhoeae urethral cultures had FVU specimens that were positive by N. gonorrhoeae PCR, by two confirmatory N. gonorrhoeae PCR assays using 165 rRNA and cytosine methyltransferase primers, and by M-PCR. The sensitivity of M-PCR for detecting C. trachomatis was 100% (22 of 22 specimens), compared with 81.8% (18 of 22 specimens) for enzyme immunoassay. Sensitivity of M-PCR for N. gonorrhoeae was 92.3% (12 of 13 specimens) compared with 84.6% (11 of 13 specimens) for urethral culture. The specificity of M-PCR was 100% for both C. trachomatis (178 of 13 specimens) and N. gonorrhoeae (187 of 187 specimens). M-PCR testing of FVU specimens provided a sensitive and noninvasive method for detecting C. trachomatis and N. gonorrhoeae infection in men.